의료영상에서 생성형 인공지능과 대형 언어 모델 입문 - 김기덕; 홍길선; 김남국; Kiduk Kim; Gil-Sun Hong; Namkug Kim (Journal of the Korean Society of Radiology, 2024)
The recent advent of large language models (LLMs), such as ChatGPT, has drawn attention to generative artificial intelligence (AI) in a number of fields. Generative AI can produce different types of data including text, images, and voice, depending on the training methods and datasets used. Additionally, recent advancements in multimodal techniques, which can simultaneously process multiple data types like text and images, have expanded the potential of using multimodal generative AI in the medical environment where various types of clinical and imaging information are used together. This review summarizes the concepts and types of LLMs, image generative AI, and multimodal AI, and it examines the status and future possibilities of generative AI in the field of radiology. 최근 ChatGPT를 포함한 대형 언어 모델의 출현으로 생성형 인공지능은 다양한 분야에 관심을 끌고 있다. 생성형 인공지능은 학습 방법과 데이터에 따라 텍스트, 이미지, 음성 등 다양한 형태의 데이터를 생성할 수 있다. 이에 더해 최근 텍스트와 이미지 등 여러 종류의 데이터를 동시에 처리할 수 있는 기술의 발달로, 다양한 임상정보와 영상정보를 함께 활용해야 하는 의료 환경에서 이러한 멀티모달 생성형 인공지능의 활용 가능성이 높아지고 있다. 본 종설에서는 대형 언어 모델, 이미지 생성 모델, 멀티모달 인공지능에 대한 개념과 종류 등에 대해 알아보고, 연구 사례를 통해 영상의학 분야에서 생성형 인공지능의 활용과 향후 가능성을 알아보고자 한다.